Perancangan dan Implementasi Animasi Interaktif sebagai Media Pembelajaran Bahasa Inggris pada Anak - Indah, Ulya; Purnawati , Ely; Marcos, Hendra (Puslitbang Sinergis Asa Professional, 2023)
English is now an international language that is used in many areas of life around the world. English is also used in communication to share knowledge around the world. So, the author made an animation program that is both interactive and can be used to teach basic English lessons. So it is useful for children to know the alphabet, numbers, names of fruits, animals, and types of vehicles. Interactive animation is a way for parents who want to teach their kids more about English to help them learn it better. Apart from being a learning tool, animation can also relieve boredom from daily activities. And, of course, the expected result is that users can improve their understanding, knowledge and vocabulary in English.